2000
DOI: 10.1074/jbc.m001499200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Analysis of the Kruppel-associated Box (KRAB) Transcriptional Repression Domain

Abstract: The Kruppel-associated box (KRAB) domain is a 75-amino acid transcriptional repressor module commonly found in eukaryotic zinc finger proteins. KRAB-mediated gene silencing requires binding to the RING-B boxcoiled-coil domain of the corepressor KAP-1. Little is known about the biochemical properties of the KRAB domain or the KRAB⅐KAP-1 complex. Using purified components, a combination of biochemical and biophysical analyses has revealed that the KRAB domain from the KOX1 protein is predominantly a monomer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
84
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 50 publications
9
84
0
1
Order By: Relevance
“…It is located at the N terminus when it is part of a zinc finger-containing transcription factor. The primary amino acid sequence of the domain does not resemble any of the other zinc finger-associated domains, such as the Kruppelassociated box (KRAB) or the poxvirus and zinc finger (POZ) domain, which is also known as the BTB (Broad-complex, Tramtrack, and Bric-a-brac) domain (7)(8)(9). Members of the SCAN domain family are broadly expressed and appear to function as either activators or repressors of transcription.…”
mentioning
confidence: 99%
“…It is located at the N terminus when it is part of a zinc finger-containing transcription factor. The primary amino acid sequence of the domain does not resemble any of the other zinc finger-associated domains, such as the Kruppelassociated box (KRAB) or the poxvirus and zinc finger (POZ) domain, which is also known as the BTB (Broad-complex, Tramtrack, and Bric-a-brac) domain (7)(8)(9). Members of the SCAN domain family are broadly expressed and appear to function as either activators or repressors of transcription.…”
mentioning
confidence: 99%
“…There exist a number of publications describing the correlation between the expression of ZNF280B and the growth of various types of cancer (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). For example, Gunn et al (22) reported that ZNF280B acts as a tumor suppressor in chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…By interacting with DNA and proteins, ZNF proteins can provide links between these molecule types (4). An increasing number of studies has reported that ZNF proteins serve critical roles in human cancers (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). For example, ZNF703 acts as an oncogene in invasive gastric carcinoma, and its expression levels are correlated with gastric carcinoma progression (16).…”
Section: Introductionmentioning
confidence: 99%
“…Repressor functions are often mediated through an interaction of the repressor domain with nuclear co-repressors. For example, the repression by the Krü ppel-associated box is mediated through interaction with the co-repressor TIF1 (4,5,65). As mentioned above, the speckled-like distribution of Glis1 in the nucleus suggests association with a larger protein complex and possibly a co-repressor complex.…”
Section: Figmentioning
confidence: 99%
“…subfamilies based on the number of zinc finger motifs, sequence homology between the zinc-fingers, and the presence of specific repressor and activation domains (3)(4)(5)(6).…”
mentioning
confidence: 99%